APPROACHES TO THE ADAPTATION OF SHONA NGOMA STYLES IN ZIMBABWEAN POPULAR MUSIC - Chamisa, Vimbai (International Library of African Music, 2017)
The focus of this article is on Zimbabwean popular songs that adapt traditional Shona ngoma (drum) genres. Its purpose is twofold. First, the article identifies Zimbabwean popular musicians' various approaches to the adaptation of traditional rhythmic patterns and song texts associated with certain ngoma genres. Second, it examines how these approaches influence the process of redefining the Shona musical tradition. It is argued that the traditional drumming patterns and styles incorporated within specific Shona popular songs have an important role in redefining this music culture within Zimbabwean popular music in general. A critical analysis is conducted on selected ngoma-influenced, Zimbabwean popular songs and the opinions expressed by the popular musicians who create the music. Three different approaches of adapting ngoma rhythms have been identified and are explained. These approaches are realised in the "integration” of musical and non-musical elements, "framework” as far as the imitation of structure is concerned, and "component”, as far as content is concerned.
Keywords: Shona (African people); Folk music; Ngoma Rhythms; Zimbabwean Popular Music; Traditional Music; Adaptation; Zimbabwe; African Music